Salivary gland proteome of the human malaria vector, Anopheles campestris-like (Diptera: Culicidae) - Sor-Suwan S. (2014)
Anopheles campestris-like is proven to be a high-potential vector of Plasmodium vivax in Thailand. In this study, A. campestris-like salivary gland proteins were determined and analyzed by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), two-dimensional gel electrophoresis, and nano-liquid chromatography-mass spectrometry. The total amount of salivary gland proteins in the mosquitoes aged 3-5 days was approximately 0.1 ± 0.05 μg/male and 1.38 ± 0.01 μg/female. SDS-PAGE analysis revealed at least 12 major proteins found in the female salivary glands and each morphological region of the female glands contained different major proteins. Two-dimensional gel electrophoresis showed approximately 20 major and several minor protein spots displaying relative molecular masses from 10 to 72 kDa with electric points ranging from 3.9 to 10. At least 15 glycoproteins were detected in the female glands. Similar electrophoretic protein profiles were detected comparing the male and proximal-lateral lobes of the female glands, suggesting that these lobes are responsible for sugar feeding. Blood-feeding proteins, i.e., putative 5′-nucleotidase/apyrase, anti-platelet protein, long-form D7 salivary protein, D7-related 1 protein, and gSG6, were detected in the distal-lateral lobes (DL) and/or medial lobes (ML) of the female glands. The major spots related to housekeeping proteins from other arthropod species including Culex quinquefasciatus serine/threonine-protein kinase rio3 expressed in both male and female glands, Ixodes scapularis putative sil1 expressed in DL and ML, and I. scapularis putative cyclophilin A expressed in DL. These results provide information for further study on the salivary gland proteins of A. campestris-like that are involved in hematophagy and disease transmission. © 2012 Springer-Verlag Berlin Heidelberg.